Association of dietary intake with pneumothorax: A Mendelian randomization study - Qichen Liang; Huimin Ma; Liming Zhang; Lu Ning; Yajun Zhao; Yang Li; Baoyu He; Aiping Yang; Ziteng Zhang (Heliyon)
Background: An association between dietary habits and lung disease has been demonstrated in previous studies. Employing Mendelian randomization, we aimed to explore how different dietary intakes relate to pneumothorax, shedding light on the interplay among gut flora, the lung-gut axis, and pneumothorax. Methods: Employing both two-sample and multi-sample Mendelian randomization (MR) analyses, we investigated 24 dietary intake variables to establish a strong association with pneumothorax. Causal inferences were drawn using the inverse variance weighted (IVW) method. To fortify our findings, we employed a diverse array of methodologies, including Weighted Median Estimator (WME), Weighted Mode, Simple Mode, Mendelian Randomization Pleiotropy Residual Sum and Outlier (MR-PRESSO), MR-Egger regression, and LASSO. Results: Our analysis identified genetic variants reliably predicting dietary intakes, meeting stringent criteria (p < 5 × 10−8) and demonstrating independence (r2 < 0.001). Causal-effect estimates derived from the IVW model unveiled a statistically significant association, indicating a causal correlation between pneumothorax and three dietary intakes. Specifically, heightened consumption of fresh fruit (OR = 0.196, 95%CI: 0.063–0.606, p = 0.004) and dried fruit (OR = 0.323, 95%CI: 0.114–0.911, p = 0.032) correlated with reduced pneumothorax risk, while increased processed meat intake (OR = 2.705, 95%CI: 1.026–7.128, p = 0.044) showed a positive correlation. Conclusion: In summary, our MR analysis yields robust evidence supporting a causal correlation between dietary elements and pneumothorax. This study significantly advances our comprehension of pneumothorax risk factors, protective agents, and the intricate mechanisms of the lung-gut axis.